The Formulation and Evaluation of Anti-Aging Tamarind Leaf (Tamarindus Indica L.) Extract Cream - Arini Miftaqul Jannah; Nurfina Aznam (Indonesian Journal of Chemistry and Environment, 2022)
This study aims to formulate and evaluate the anti-aging tamarind leaf (Tamarindus Indica L.) extract cream due to the increasing demand for the anti-aging product day by day. In this study, tamarind leaf extract was tested to find out its phytochemicals, antioxidant activity using a 1,1-diphenyl-2-picrylhydrazyl method, and anti-aging activity using a UV spectrophotometer. Anti-aging cream was formulated based on the antioxidant and anti-aging potential of tamarind leaf extract and its evaluation. The cream was formulated with tamarind leaf extract, carboxymethylcellulose, and base cream with different emulsion types (water in oil and oil in water). This study revealed that tamarind leaf extract contains alkaloid, flavonoid, saponin, phenol, and tannin. Tamarind leaf extract also has an antioxidant and an anti-aging activity. The cream evaluation showed that cream with extract concentration at 80 ppm emulsion types W/O and O/W placed in outdoor and indoors were to be stable during 4 weeks of stability studies. The creams still have antioxidant activity, do not experience a significant change in their physical appearance at organoleptic test, homogeny, pH range at 4.5-8, spreadability range at 5-7 cm in weight 0-50 gram, and are not separated during centrifugation test.